(untitled) (Tempo e Argumento, 2009)
During the first decades following World War II, population history was dominated by the model of “historical demography” designed by Louis Henry at INED, and taken over by Fernand Braudel and the Annales school. But in the 1980s, the Henry model was called into question by deconstructionist approaches derived from Michel Foucault, and by critics against objectivism. At the same time, history of statistics discovered the ambiguous ideological roots of demography (pronatalism, eugenics, biopolitical thought). To pick up again, the discipline introduced new methods (micro-history) and new issues (institutions). As a result, nowadays, historical demography is more and more replaced by a social and political population history. It focuses on how institutions, policies and knowledge devoted to populations construct each other in an interactive, simultaneous process. Condorcet, who was fought against by Malthus; Achille Guillard, who coined the word "demography”, and of course the durkheimian sociologist Maurice Halbwachs, have formalised the "social" dimension of population. Contrary to current sociobiological temptations, the deep, organic tie between population and social protection raises the fundamental issue of how society endlessly shapes itself.